The Information System Of Name Card Sales Based On Digital Marketing To Improve Creativepreneur On College E-Commerce Website - Santoso, Sugeng; Kauf, Josch; Aristo, Nabila Cynthia (Aptisi Transactions On Technopreneurship (ATT), 2019)
Advances in technology and information have abundant benefits, especially in the business of business card services by utilizing e-commerce. When buying a business card, the buyer can order a business card by contacting the seller directly, then the order is processed to completion and finally reaches the buyer. However, this method is not in line with current technological advancements because it still uses conventional transaction processes. Therefore, to overcome this problem an e-commerce website is used that can process transactions accurately and quickly. In this study, there are 3 (three) problems that will be overcome with 2 (two) methods, and 3 (three) solutions are produced. The advantage of e-commerce website is that it can be accessed anytime and anywhere, so it is concluded that the use of e-commerce websites is able to overcome the problems found in business cards, business services and develop creativepreneur in Raharja Higher Education.